The impact of an interdisciplinary co-creation teaching model on the design and creative abilities of college students in a smart classroom environment - Tian, Kun; Phongsatha, Thanawan; Phongsatha, Satha (International Journal of Innovative Research and Scientific Studies, 2024)
The aim of this study was to investigate the impact of the interdisciplinary co-creation teaching model on students’ design creativity and learning perception within a smart classroom environment. Eighty participants were randomly selected from a Chinese university and assigned to either the experimental or control group in this quasi-experimental study. Students in the control group were instructed with an interdisciplinary teaching model in the traditional classroom while respondents in the experimental group were taught with an interdisciplinary co-creation teaching model in a smart classroom environment. The two groups’ differences in perceptions of learning and design creativity were measured using pre- and post-tests. Independent t-test samples were used to analyze data for design creativity and paired sample t-tests were used for learning perception. The results showed that there are significant differences between the impact of the interdisciplinary teaching model used in a traditional classroom environment and the interdisciplinary co-creation teaching model used in a smart classroom environment on students’ design creativity and learning perception. The latter approach was found to be more effective in improving students’ design creativity and learning perception. It can be seen that the interdisciplinary co-creation teaching model in the smart classroom environment is not only a teaching tool but also a new teaching model. It allows students to obtain comprehensive learning and perception improvements during the learning process thereby improving students’ design creativity.